2005
DOI: 10.1677/jme.1.01594
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human myometrial target genes of the cAMP pathway: the role of cAMP-response element binding (CREB) and modulator (CREMα and CREMτ2α) proteins

Abstract: AbstractcAMP-response element (CRE) binding (CREB) and modulator (CREM) proteins, activated by protein kinase A-mediated phosphorylation, bind as homo-and heterodimers to promoters containing CRE and activator protein 1 (AP-1) sites to alter target-gene expression. We have previously reported differential expression of CREB and CREM splice variants CREM and CREM 2 in human myometrium during pregnancy and labour. Via microarray studies with cultured myometrial cells stably transfected with CREB, CREM and CREM 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…It is therefore interesting to note the increased expression of oestrogen receptor 2 (ESR2/ESR-beta) with over-expression of ATF2, and to compare this to the detected increase in expression of the alternative oestrogen receptor 1 (ESR1/ESR-alpha) associated with over-expression of the ATF2-related bZIP transcription factor CREB in myometrial cells (Bailey et al 2004), which has been found to be prevalent in the non-pregnant myometrium but almost absent in pregnant non-labouring and spontaneous labouring tissue (Bailey et al 2000). Interestingly, a significant minority of genes found to be affected by the over-expression of ATF2 and ATF2-sm in myometrial cells in this study are also affected by CREB (Bailey et al 2004): 25% of the genes affected by ATF2, and 38% of the genes affected by ATF2-sm.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore interesting to note the increased expression of oestrogen receptor 2 (ESR2/ESR-beta) with over-expression of ATF2, and to compare this to the detected increase in expression of the alternative oestrogen receptor 1 (ESR1/ESR-alpha) associated with over-expression of the ATF2-related bZIP transcription factor CREB in myometrial cells (Bailey et al 2004), which has been found to be prevalent in the non-pregnant myometrium but almost absent in pregnant non-labouring and spontaneous labouring tissue (Bailey et al 2000). Interestingly, a significant minority of genes found to be affected by the over-expression of ATF2 and ATF2-sm in myometrial cells in this study are also affected by CREB (Bailey et al 2004): 25% of the genes affected by ATF2, and 38% of the genes affected by ATF2-sm.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids and Luciferase Assays-An expression plasmid for human CREM␣ (in the pcDNA3.1/V5-His-TOPO vector, Invitrogen) was kindly provided by G. N. Europe-Finner (Faculty of Medical Sciences, Newcastle upon Tyne, United Kingdom) (29). A 2.1-bp spanning Notch-1 reporter construct (in pGL3-Basic vector, Promega) was generated and kindly donated by M. Ruppert (University of Alabama at Birmingham) (30).…”
Section: Methodsmentioning
confidence: 99%
“…An issue key to the current study is how myometrial hIP/PKA signaling may effect changes in the expression of SM2-MHC, h-caldesmon, calponin, a-SMA, and connexin 43. However, cAMP elevation instigates a wide variety of transcriptional events in many cells and tissue types, including myometrium (5). Given the pleiotropic nature of such cAMP-mediated regulation, one wonders whether other receptor-coupled stimuli (e.g., β-adrenergic agonists, prostaglandin E2, etc.)…”
Section: Prostacyclin Signaling Via Camp and Pkamentioning
confidence: 99%
“…In fact, early observations that the uterine environment is rich in hematopoietic growth factors/cytokines (whose expression in many cases is regulated by the ovarian sex steroid hormones 17β-estradiol and progesterone), coupled with the observation of the dynamic recruitment of diverse innate immune cells, led to the proposal that these immune cells play an important role in decidual and placental development (2,3). Among the earliest growth factors expressed in the uterus are GM-CSF and CSF-1, which regulate the myeloid system (4,5). Levels of CSF-1 synthesized by the uterine epithelium are elevated at the time of implantation and continue to climb dramatically throughout the process of placentation (4).…”
Section: Successful Embryo Implantation Requires Complex Interactionsmentioning
confidence: 99%